2022
DOI: 10.3390/pharmaceutics14040843
|View full text |Cite
|
Sign up to set email alerts
|

Application and Multi-Stage Optimization of Daylight Polymer 3D Printing of Personalized Medicine Products

Abstract: Additive technologies have undoubtedly become one of the most intensively developing manufacturing methods in recent years. Among the numerous applications, the interest in 3D printing also includes its application in pharmacy for production of small batches of personalized drugs. For this reason, we conducted multi-stage pre-formulation studies to optimize the process of manufacturing solid dosage forms by photopolymerization with visible light. Based on tests planned and executed according to the design of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Personalized medicine entails tailoring drug treatment, dosing intervals, drug combinations, and drug release rates to account for individual needs [ 72 ]. Nanotechnology, on the other hand, has played a key role in the development of novel drug delivery systems to meet the needs of individuals, contrary to the ‘one-size-fits-all’ hypothesis.…”
Section: 3d Printing Technology To Design Nanomedicine-based Solid Do...mentioning
confidence: 99%
“…Personalized medicine entails tailoring drug treatment, dosing intervals, drug combinations, and drug release rates to account for individual needs [ 72 ]. Nanotechnology, on the other hand, has played a key role in the development of novel drug delivery systems to meet the needs of individuals, contrary to the ‘one-size-fits-all’ hypothesis.…”
Section: 3d Printing Technology To Design Nanomedicine-based Solid Do...mentioning
confidence: 99%
“…Pyteraf et al studied the use of vitamin C instead of TEOHA as co-initiator for RF in LCD 3D printing of mebeverine hydrochloride loaded hydrogels, and concluded that it leads to irregular, unreproducible results. 38 Furthermore, RF can be used to fabricate bioscaffolds for tissue engineering. Riboflavin-5'-phosphate (the coenzyme flavin mononucleotide, FMN) with TEOHA was applied in 2PLP of PEGDA to yield biocompatible scaffolds with high printing precision.…”
Section: Organic Materials Thiemementioning
confidence: 99%
“…Additionally, recent works have been taken advantage of the biocompatibility of RF to produce hydrogels for extended and/or controlled drug release. [34][35][36][37][38] Martinez et al used the RF-TEOHA system for the fabrication of SLA 3D-printed ibuprofen-loaded PEGDA hydrogels. 34 Along these lines, Madzarevic et al prepared ibuprofen-loaded hydrogel tablets using DLP and LCD 3D printing at 405 nm.…”
Section: Riboflavinmentioning
confidence: 99%
See 1 more Smart Citation